2020
DOI: 10.1186/s13048-020-00678-9
|View full text |Cite
|
Sign up to set email alerts
|

Salpingectomy may decrease antral follicle count but not live birth rate for IVF-ET patients aged 35–39 years: a retrospective study

Abstract: Purpose: Problems with fallopian tubes are one of the main reasons for women to undergo in vitro fertilizationembryo transfer (IVF-ET). A large proportion of women with ectopic pregnancy, fallopian tube obstruction and hydrosalpinx have had one or both fallopian tubes removed by salpingectomy. With increasing age, ovarian reserve deteriorates, the numbers of retrieved oocytes, available embryos and high-quality embryos are reduced, and the live birth rate for women treated with IVF treatment is affected. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…For women with an optimal ovarian reserve and a large follicle pool, a history of salpingectomy did not affect the number of retrieved oocytes in subsequent IVF cycles. Similar results were observed in a retrospective study [ 13 ], which revealed that in IVF patients aged 35–39 years, the AFC was lower in patients with a history of salpingectomy than in those without a history of salpingectomy; however, the study did not further stratify patients under the age of 35 with distinct baseline ovarian reserves. Moreover, in the study of Chen et al, the researchers selected patients with tubal disease as controls, which may have lessened the effect of salpingectomy, for underlying tubal disease may have been a confounding factor for reduced ovarian reserve.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For women with an optimal ovarian reserve and a large follicle pool, a history of salpingectomy did not affect the number of retrieved oocytes in subsequent IVF cycles. Similar results were observed in a retrospective study [ 13 ], which revealed that in IVF patients aged 35–39 years, the AFC was lower in patients with a history of salpingectomy than in those without a history of salpingectomy; however, the study did not further stratify patients under the age of 35 with distinct baseline ovarian reserves. Moreover, in the study of Chen et al, the researchers selected patients with tubal disease as controls, which may have lessened the effect of salpingectomy, for underlying tubal disease may have been a confounding factor for reduced ovarian reserve.…”
Section: Discussionsupporting
confidence: 85%
“…In a study comparing women with infertility with and without history of salpingectomy for known tubal disease [ 13 ], history of salpingectomy was associated with a lower antral follicle count (AFC) in the women with infertility who were 35–39 years old. The study did not report a reduction of AFC related to a history of salpingectomy in women under 35 years old, implying that decline in age-related ovarian reserve may contribute to the impairment of ovarian reserve in women with a history of salpingectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is reasonable to consider that prophylactic bilateral salpingectomy may prevent ovarian cancer without the risk of premature menopause. However, other studies have found that bilateral salpingectomy alone or combined with hysterectomy could increase the risk of menopausal symptoms or decrease the antral follicle count (AFC) after surgery [ 10 , 11 ]. Some researchers have expressed concern about postsurgical ovarian function since fallopian tubes and their surroundings might have contributed to the ovarian blood supply.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to consider that prophylactic bilateral salpingectomy may prevent ovarian cancer without the risk of premature menopause. However, other studies have found that bilateral salpingectomy alone or combined with hysterectomy could increase the risk of menopausal symptoms or decrease the antral follicle count (AFC) after surgery [10,11]. Patients are understandably concerned about the effects of bilateral salpingectomy, but relatively few studies have been conducted in China to assess the risks and bene ts of the procedure.…”
Section: Introductionmentioning
confidence: 99%